Patient Satisfaction With Health Care Services In Outpatient Department Of A Dental College Hospital In Pakistan (Update Dental College Journal, 2018)
Introduction: Patient satisfaction is one of the important factors to determine the success of health care facility. The real challenge is not getting ready with mere requirements, but also delivers services ensuring good quality. Thus, there is a need to assess the health care systems regarding patient satisfaction as often as possible. The aim of this study was to determine the patient satisfaction with health care services in out-patient department (OPD) of a dental college hospital in Pakistan.Materials and Methods: A descriptive cross-sectional pilot study was undertaken during the month of May 2015 in the OPD of Bibi Asifa Dental College and Hospital, Larkana, Pakistan. A randomly selected 100 patients were interviewed by using pre-structured questionnaires. The questionnaires had semi-structured, open-ended and closed questions. While analyzing, they were grouped into categories like availability of services, clinical care, waiting time and cost.Results: The overall opinions about the satisfaction level of patients for availability of health services in the hospital were good. As location of the hospital and timings of the OPD were convenient to the most of the patients 86% and 93% respectively. Availability of the doctors was also found adequate. However, regarding seating arrangements one fourth of the total patients were found to be unsatisfied. Efficiency of the doctor was found satisfactory by 83%, while majority of the patients did not faced any kind of language problem.Conclusion: According to patient’s opinion, the study revealed that the degree of satisfaction was satisfactory with respect to waiting time and availability of the doctors in the hospital, which need to be further explored and corrected.Update Dent. Coll. j: 2018; 8 (1): 55-60